Asinan Nanas Upaya Peningkatan Nilai Jual Nanas Madu Di Desa Tanah Tinggi - Aliyanti Aliyanti Zumrona; Dias Boy; Joko Saputra; Lia Ismi Kandini; Samuel Hadiyanto; Anggi Mandala Putra; Eko Sumartono (Jurnal Dehasen Untuk Negeri, 2023)
Asinan pineapple is one example of the diversity of culinary snacks in Indonesia made from fresh pineapple. Pineapple pickles, besides being rich in benefits, can also be a solution to the problem of low selling value complained about by farmers. In addition to being able to increase the selling value, the pineapple pickle business also has a great opportunity, this is supported by the sweet and sour taste which is a flavor that is much loved by people both among young people, mothers to students. As a business, the capital required to start a pineapple pickle business is also not too expensive. This is due to the abundant amount of pineapple, affordable prices, and the ingredients needed are not too many. Therefore, the pineapple pickle business, especially in the urban area of Bengkulu, is very promising, supported by the hot weather. Business activities are carried out at the residence of one of the members who resides in Vila Pematang Indah, Pematang Gubernur. The choice of this place was based on the consideration that the location is a large location that facilitates the production process. Meanwhile, Tanah Tinggi Village, Padang Jaya Sub-district, North Bengkulu is the location where raw materials are collected.1. Strength Pickled pineapple has a price that is affordable by all people. Pineapple as raw material is easy to obtain, especially in Tanah Tinggi Village, Padang Jaya District, Bengkulu Utar which is the center of pineapple plantations. 2. Weakness Cannot be consumed in excess because it causes infections in the mouth and stomach. 3. Opportunity The high consumer appetite for the combination of salty and spicy flavors found in pineapple asians 4. Threat The high cost of transportation from the raw material supplier to the production site. There are processed pickled businesses from other fruits. This pineapple fruit pickled business is good for attracting consumers because it is unique and there are still few who use pineapple as a pickled ingredient. With varying cup sizes, of course, this will increase consumer interest in choosing these products. The need for vitamins and various benefits of consuming pineapple fruit can be found through these preparations, one of which is good for the body's metabolism, but sometimes people are very lazy to consume it in its whole form because of boredom, therefore this is a processing creation with a new variant so that people do not feel bored to consume pineapple fruit.